Enzymatic synthesis of epoxy fatty acid starch ester in ionic liquid-organic solvent mixture from vernonia oil - Desalegn, Tegene; Villar-García, Ignacio J.; Titman, J.; Licence, Peter; Díaz Carretero, Isabel; Chebude, Yonas (Starch - Stärke, 2014)
In this study, epoxy fatty acid esters of cassava starch were synthesized by reacting cassava starch with vernonia oil methyl ester (epoxy ester) using 1‐butyl‐3‐methylimidazolium hexafluorophosphate, [C4C1Im][PF6] ionic liquid (IL) as a reaction medium and DMSO as co‐solvent. Lipase Candida antarctica fraction B (Novozyme 435) was used as a catalyst for the esterification reaction. In the optimized reaction conditions, a degree of substitution (DS) of 0.95 was achieved, at a reaction temperature of 40°C within 72 h of reaction time. The new cassava starch esters were characterized by infrared (FTIR), solid state NMR (CP/MAS 13C NMR), SEM, XRD, thermogravimetric analysis (TGA), and DSC. FTIR and NMR spectroscopy analyses confirmed the successful esterification of starch and the DS was calculated to be 0.95 by titration methods. SEM and XRD studies showed that the morphology and crystallinity of native cassava starch were significantly changed upon esterification producing a continuous and amorphous material. Finally, the thermal behavior of the native and the starch vernolate was investigated using TGA and DSC techniques. The results revealed a change in the characteristic melting point and decomposition pattern of the new polymer. The onset decomposition temperature of the new starch vernolate is similar to the native form. The authors thank the School of Chemistry, University ofNottingham, UK for the provision of all instrumentation for thiswork and for partial funding of TD. We are most grateful to Dr.Jeremy Titman for the13C solid-state CP-MAS NMR analysesand helpful discussions. IJVG, YC, and ID acknowledge theSpanish Research Council (CSIC) for funds through theprogramme CSIC for development, project number i-COOP014.The Chemistry Department, Addis Ababa University is alsoacknowledged forfinancial support. Peer Reviewed